2005
DOI: 10.3354/dao064127
|View full text |Cite
|
Sign up to set email alerts
|

Role of cellular response in elimination of the monogenean Neoheterobothrium hirame in Japanese flounder Paralichthys olivaceus

Abstract: Adult worms of the blood-feeding monogenean parasite Neoheterobothrium hirame, which cause anemia in the Japanese flounder Paralichthys olivaceus, attach to the host fish by embedding their posterior part deeply into the host tissue. To investigate the possibility that cellular responses of the host fish can eliminate N. hirame, flounder were experimentally infected with N. hirame larvae and reared in either fed or starved conditions. Mature parasites were identified on the buccal cavity wall of the fish 33 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…This parasite has serious impacts (anemia and reduction in somatic condition) on Japanese flounder populations in other localities (Shirakashi et al 2006). Japanese flounder can resist N. hirame infection by feeding sufficiently (Nakayasu et al 2005), and our results reflect the high food availability in the study area. The presence of anchovy and sandlance strongly support the production of piscivorous fishes.…”
Section: Discussionsupporting
confidence: 52%
“…This parasite has serious impacts (anemia and reduction in somatic condition) on Japanese flounder populations in other localities (Shirakashi et al 2006). Japanese flounder can resist N. hirame infection by feeding sufficiently (Nakayasu et al 2005), and our results reflect the high food availability in the study area. The presence of anchovy and sandlance strongly support the production of piscivorous fishes.…”
Section: Discussionsupporting
confidence: 52%
“…These cells communicate to eliminate the parasites through various cytokines, which results in the production and release of hostile molecules (Buchmann 1999). As reported by Nakayasu et al (2005), N. hirame induces inflammatory reactions at the infected site. Further study focusing on the reaction at the site of infection should be conducted to improve our understanding of the host-parasite interaction.…”
Section: Resultssupporting
confidence: 54%
“…The parasite causes necrosis and intensive infiltration of inflammatory cells in tissues around the attachment sites. Nakayasu et al (2005) suggested that monocytes/macrophages, granulocytes and cells with large, electron-dense granules may possibly be involved in the elimination of the parasite by cellular response, because these cells infiltrated and directly adhered to the parasites, and destroyed the integument and inner tissue of the parasites. There is no doubt about the involvement of leucocytes in the host response, but their role in the defense activity against N. hirame is unclear.…”
Section: Abstract: Japanese Flounder · Neoheterobothrium Hirame · MImentioning
confidence: 99%
“…This would explain the significant monocytes increase in the cold season. Monocytes play an important role in host defense against parasites, by infiltrating the damaged tissue and by adhering to the pathogen (NAKAYASU et al, 2005). Considering the negative correlation between the number of monocytes and parasitism by Monogenea in cold season, it can be assumed that this relationship is due to the migration of monocytes to the injured site when parasitism increases.…”
Section: Discussionmentioning
confidence: 99%